Effectiveness and safety evaluation of terlipressin in the treatment of intestinal paralysis in end-stage liver disease - Xia Wan; Hua Xu; Hu Li; Shan Zhong; Yu Lei; Huan Deng; Xiao Fu; Zhi Zhou (BMC Gastroenterology)
Abstract Background and aims Intestinal paralysis is a common complication in end-stage liver disease (ESLD), our aim is to assess the effectiveness and safety of low-dose terlipressin for treating intestinal paralysis in ESLD. Methods The study was divided into two phases, in the exploratory phase, we retrospectively analyzed the clinical data of patients with intestinal paralysis treated with low-dose terlipressin and explored its efficacy. In the clinical research phase, we designed a prospective cohort study, patients with intestinal paralysis were categorized into terlipressin treatment group (low-dose terlipressin was added to the conventional treatment) and conventional treatment group according to their wishes. The remission of intestinal paralysis, time to symptom remission, and differences in adverse reactions were compared between the two groups. Results In the exploratory phase, 26 patients were exposed to low-dose terlipressin, 12 were cured, 11 were moderately effective, and 3 were ineffective. The mean time to abdominal bloating remission was 2 days, and the time to anal flatus and feces passage was 1 day. In the clinical research phase, a total of 131 patients were included at baseline, with the exception of one patient who discontinued medication due to severe vomiting, resulting in a final total of 130 patients included in the analysis. The mean time to abdominal pain and bloating remission in the terlipressin treatment group (32/130) was demonstrably shorter compared to the conventional treatment group (98/130) (P < 0.001), the mean time to anal flatus and feces passage was also shorter (P < 0.001), and the remission rate was higher (P < 0.05). The incidence of adverse events was similar. Conclusions Low-dose terlipressin treatment could considerably increase intestinal paralysis remission in ESLD patients with intestinal paralysis, and have good safety.